Digital shift in ELT: Impact of technology on Indonesian high school students’ language proficiency - Anwar, Choiril; Hartono, Hartono; Pek, Lim Seong; Yavuz, Fatih; Nugroho, Kurniawan Yudhi; Ilmi, Isna Nuzullul (JEES (Journal of English Educators Society), 2026)
The use of technology in English Language Teaching (ELT) has revolutionized the field of education by providing previously unheard-of chances for language acquisition. High school students in Indonesia who are learning English as a foreign language (EFL) stand to gain a great deal from technology-enhanced training. The purpose of this research is to examine how technology-enhanced instruction affects the language competency and learning outcomes of high school students in Indonesia. A quantitative method was used. Thirty-one Indonesian high school students were selected for the study using stratified random sampling. Speaking, reading, and writing language competency tests were among the ways used to obtain the data. Statistical Packages for Social Sciences (SPSS) version 25 was used for data analysis, which included descriptive statistics and inferential statistics (t-tests). This study shows how technology-enhanced instruction can transform ELT in Indonesian high schools and offers stakeholders, educators, and policy-makers useful information for creating successful language learning initiatives. The results highlight the significance of using technology to improve language learning outcomes and have ramifications for language instruction around the world.